2006
DOI: 10.1590/s0066-782x2006001600005
|View full text |Cite
|
Sign up to set email alerts
|

Cirurgia de revascularização na fase aguda do infarto do miocárdio: análise dos fatores pré-operatórios preditores de mortalidade

Abstract: M a i l i n g A d d r e s s : OBJECTIVETo assess preoperative predictors of mortality in patients undergoing coronary artery bypass grafting (CABG) within the first 30 days of acute myocardial infarction (AMI). METHODSBetween March 1998 and July 2002, 753 AMI patients were consecutively and prospectively entered into a database, 135 (17.9%) of whom underwent isolated CABG and were enrolled in this study. The following prognostic factors were assessed by multivariate analysis: age, gender, diabetes, history of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…But he noted that these variables did not show differences in mortality in this group of patients [15].…”
Section: Discussionmentioning
confidence: 75%
“…But he noted that these variables did not show differences in mortality in this group of patients [15].…”
Section: Discussionmentioning
confidence: 75%
“…and Ladeira et al . [ 17 18 ] These investigators prospectively analyzed 4090 patients who underwent CABG after MI and divided them into three groups based on the MI-to-CABG intervals of 0–30 days, 31–90 days, and >90 days. Their 5-year survival rates were 85.5%, 85.2%, and 89.3%, respectively, with no significant difference among the three groups.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 14 15 ] Although the latest American College of Cardiology (ACC)/American Heart Association guidelines for CABG surgery provided specific recommendations for surgical revascularization after STEMI, the optimal timing of CABG after AMI is still not well defined according to previous studies. [ 16 17 18 19 ] Some studies recommended that an interval of at least 1 week between STEMI and surgical revascularization was relatively safe. [ 20 ] However, other studies have demonstrated that CABG can be performed at any time after STEMI.…”
Section: Introductionmentioning
confidence: 99%